MANAJEMEN KEWIRAUSAHAAN DI DAYAH SERAMBI ACEH - Hardianty, Sri; Saleha, Fitri; Agustina, Maya (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2024)
Abstract Etrepreneurship management, especially in an educational organization, is the creative and innovative use of economic potential with the courage to face risks to gain profits that are useful for the success of the program in the educational organization. One of the Dayah that develops entrepreneurial management is Dayah Serambi Aceh. There are several types of businesses run by Dayah Serambi Aceh, namely grocery stores, bookstores and hardware store. This research aims to determine the entrepreneurship management carried out by Dayah Serambi Aceh which includes the functions of planning, implementation, supervision and evaluation as well as to determine the obstacles faced by managers in carrying out entrepreneurial activities. This research used a qualitative approach with seven research subjects. The data collection techniques are through interviews, observation and documentation. The results of the research show that the entrepreneurship planning carried out by Dayah Serambi Aceh includes planning the type of business, the amount of business capital, the location of the business and the schedule for implementing the business. Then implementation is carried out by establishing a work contract for managers for each business with an incentive distribution of 60% of profits for Dayah Serambi Aceh and 40% of profits for managers calculated from annual sales profits. Furthermore, supervision is carried out by the leadership of Dayah Serambi Aceh by making regular visits to each business. And evaluation is carried out by assessing business performance, determining business development prospects and fixing things that are still obstacles in carrying out entrepreneurial activities. The obstacles faced by business managers are insufficient knowledge and expertise in the field of entrepreneurship and marketing reach which is still narrow in scope.